5G Awareness and its Link to COVID-19: Case of Zambians with Access to Internet - Chembe, Christopher; Banda, Alick; Kalezhi, Josephat; Kunda, Douglas (Zambia ICT Journal, 2021)
Fifth Generation (5G) mobile cellular networks are envisaged to provide for high data rates and very low delay to support a lot of applications. However, its deployment has been met with a lot of resistance from some members of the public in various countries around the globe. This resistance has been exacerbated by the onset of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which has since been named COVID-19. Since the beginning of December 2019, COVID-19 has spread rapidly around the world with increased discussions on the topic across various online platforms. Due to the nature of these online platforms, misinformation is greatly shared and it becomes difficult for policy makers to implement measures that could save lives. For example, there have been conspiracy theories that were circulating on social media platforms perpetuating that radiation from 5G towers are linked with symptoms associated with COVID-19. This information led to some people burning 5G towers in certain countries. Basic awareness of 5G technology and its related health concerns should be made available to the general public. Therefore, this research highlights general health concerns about 5G technology based on various research conducted. Furthermore, the paper presents results from an online survey with a total of 258 respondents. Results show that 67% of respondents are aware of 5G technology and most users get there information from online social media platforms (about 78%). About 62% of respondents have heard the conspiracy theories linking 5G to COVID-19 symptoms, however, only 14.3% believe the conspiracy. Interestly, 57.8% think coronavirus originated from the laboratory and 47.3% think the COVID-19 pandemic was planned by certain pharmaceutical corporations and government agencies to depopulate the world. Additionally, 43% of respondents think there is no good reason for the current lock-down by various governments. Results also shows that there is no link between 5G and COVID-19 as far as health issues are concerned.